Cineinstalações e o processo de criação no atravessamento dos espaços em ambientes audiovisuais e interativos: uma cartografia de poéticas experimentais - Villavicencio, Pablo Souza de (2015)
This doctoral thesis analyses the contemporary audiovisual trend called cinema installation. It examines a few projects dealing with the relationship between space, audiovisual and spectator (interactor) that make up artistic environments. Equally, it emphasises the building of a space in body movements and interactors gestures, such as the audiovisual temporality and interactivity, focusing on man-machine interface. Cinema installations can include: a) the "multi-screen cinema", invented by Abel Gance, with the film Napoleon (1927); b) immersive environments, e.g., Stan Vandereek s Movie-drome (1963-65), c) immersing and interactive environments, e.g., Jeffrey Shaw s Place Ruhr (2000). Some concepts discussed in this study are: the database as a particuliar cultural form of digital media, the spatial editing, replacing sequential editing from traditional cinema (Manovich); the transcinema (Maciel) and the on-going cinema (Parente). Claire Bishop s art installation; Katja Kwastek s aesthetics of interactivity in digital art,; and Frank Popper s artistic environments and aesthetic-technological logic are also investigated. During the archaeological reading path of cinema installation the origins of immersive environments are considered from a Virtual Art perspective (Grau).The method comprises: a) literature review of texts that discuss poetical forms in interactive audiovisual environments; b) critical discussion of networking concepts that help elaborating the definition of cinema installation; c) research, selection and mapping of works, according to the proposed mapping poetry of Lucia Leão; d) analysis of selected works. The results achieved through the research were: critical reading of the concepts and proposals related to the language of audiovisual and interactive installations, and of expanded cinema (Youngblood); developing a concept of cinema installation; cartography of experimental projects named as cinema installation poetry ; analysis of projects; and finally